ADAB SEBAGAI FONDASI ILMU: PERSPEKTIF SYED MUHAMMAD NAQUID AL-ATTAS TERHADAP KRISIS PENDIDIKAN MODERN - Jami’atul Husna; Sekar Ardhanun; Abdurrahmansyah, Muhamad Fauzi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This article discusses the concept of adab according to Syed Muhammad Naquib al-Attas and its relevance to the crisis in modern education. Adab is understood as the main foundation in the educational process, which focuses not only on the transfer of knowledge, but also on character, moral, and spiritual development. Through a qualitative approach using library research methods, this article examines al-Attas' major works as well as data from UNESCO, the OECD, the Pew Research Center, the World Economic Forum, the UNDP, and other contemporary research. The results of the study show that the loss of adab values in modern education has led to a moral, ethical, and social crisis despite academic and technological progress. Conversely, adab-based education has been proven to shape intelligent, ethical, and responsible individuals. Thus, al-Attas's views provide an important solution to the challenges of modern education.